FAKTOR-FAKTOR YANG MEMPENGARUHI FRAUDULENT FINANCIAL REPORTING DALAM PERSPEKTIF FRAUD PENTAGON (Studi Empiris Pada Sektor Perbankan Yang Terdaftar di di Bursa Efek Indonesia Tahun 2014-2017) - Normita Normita; Ruhul Fitrios; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research was examined factors affecting fraudulent financialreporting in the perspective of the pentagon fraud at perbankan sector listed onbei in years 2014-2017. The population in this study are all PerbankanCompanies listed on BEI in years 2014-2017. This research is included inquantitative research. The type of data used in this study is secondary data fromof annual reports of companies. The sample selection in this study uses purposivesampling method where from 44 selected populations according to the samplecriteria of 35 selected companies. These data were analyzed using multipleregression analysis with SPSS Version 25. The results of this study showed thatFinancial Target affects Fraudulent Financial Reporting, External Pressureaffects Fraudulent Financial Reporting, Opportunity affects Fraudulent FinancialReporting, Rationalization affects Fraudulent Financial Reporting, Capabilityaffects Fraudulent Financial Reporting and Arrogance not affects FraudulentFinancial Reporting.Keywords : Fraudulent Financial Reporting Financial Target, External Pressure,Opportunity, Rationalization, Arrogance.